2014
DOI: 10.1038/ncomms4910
|View full text |Cite
|
Sign up to set email alerts
|

Chiral spin torque arising from proximity-induced magnetization

Abstract: Domain walls can be driven by current at very high speeds in nanowires formed from ultra-thin, perpendicularly magnetized cobalt layers and cobalt/nickel multilayers deposited on platinum underlayers due to a chiral spin torque. An important feature of this torque is a magnetic chiral exchange field that each domain wall senses and that can be measured by the applied magnetic field amplitude along the nanowire where the domain walls stop moving irrespective of the magnitude of the current. Here we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
186
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 237 publications
(201 citation statements)
references
References 37 publications
14
186
1
Order By: Relevance
“…To maximize the spin-Hall signal, the thickness of the NM exceeds in most experiments the spin diffusion length, λ sf , of the NM. However, when a thin NM (thickness below λ sf ) is placed in contact with a FM, interface effects, such as spin-memory loss [13,19] and magnetic proximity effects [20][21][22][23][24], can become pronounced and alter the spin-transport properties of the sample. Among the materials studied for large spin-Hall effects, Pt and Pd are two of the most popular metals employed, especially Pt, which has been indispensable in the establishment of virtually all the newly discovered pure spin-current phenomena [4,5,[9][10][11][12][13]16].…”
Section: Introductionmentioning
confidence: 99%
“…To maximize the spin-Hall signal, the thickness of the NM exceeds in most experiments the spin diffusion length, λ sf , of the NM. However, when a thin NM (thickness below λ sf ) is placed in contact with a FM, interface effects, such as spin-memory loss [13,19] and magnetic proximity effects [20][21][22][23][24], can become pronounced and alter the spin-transport properties of the sample. Among the materials studied for large spin-Hall effects, Pt and Pd are two of the most popular metals employed, especially Pt, which has been indispensable in the establishment of virtually all the newly discovered pure spin-current phenomena [4,5,[9][10][11][12][13]16].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been found that different choices of 5d heavy metal layers can significantly influence the sign and strength of the DMI. 3,16,[18][19][20][21] In addition, the DMI can be tailored by adjusting the ratio of film thicknesses of top and bottom nonmagnetic layers in sandwich structures. 2,22,23 However, experimental measurements of the influence of 3d elements on the DMI remain rare.…”
mentioning
confidence: 99%
“…Second, it is also responsible for the emergence of interfacial DzyaloshinskiiMoriya interaction (DMI), which promotes chiral magnetic textures. The concurrence of antidamping SOT and DMIinduced chiral textures results in fast DW motion in ultrathin layer structures [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%